2005
DOI: 10.1093/humrep/dei081
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy may be justified after two miscarriages

Abstract: BACKGROUND: Recurrent pregnancy loss is traditionally investigated after three or more consecutive pregnancy losses. Although there is a trend to start investigation after two miscarriages, data are not available to date to justify this approach. We sought to compare the frequency of uterine anomalies between women referred to hysteroscopy for repeated miscarriages after two, and three or more, miscarriages respectively. METHODS: A retrospective analysis of acquired and congenital uterine anomalies in all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 22 publications
(23 reference statements)
7
28
0
2
Order By: Relevance
“…Recently, it had been reported, after various trials on human endometria, that increased apo-lipoprotein A1 level is linked to recurrent miscarriages and also unexplained infertility [2,14]. It was revealed that apo-lipoprotein A1 is exhausted by pre-implantation embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it had been reported, after various trials on human endometria, that increased apo-lipoprotein A1 level is linked to recurrent miscarriages and also unexplained infertility [2,14]. It was revealed that apo-lipoprotein A1 is exhausted by pre-implantation embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, embryos that have highest probability of implantation exhaust or consume apo-lipoprotein A1, which compose an encouraging microenvironment in the endometrium with less apo-lipoprotein A1 values for probable implantation. Apo-lipoprotein A1 is more manifested in nondecidualized endometria when compared to a decidualized stroma [14]. So, cricial negative impacts might be anticipated for apolipoprotein A1 in augmenting and maintaining an implantation window.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies performed on human endometrial samples have revealed that elevated apolipoprotein A1 levels are associated with unexplained infertility and also repeated implantation failure [2,14]. Nyalwidhe et al [13], demonstrated that apolipoprotein A1 is consumed by human preimplantation embryos suggesting a possible role in implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, embryos with the highest likelihood of implantation consume or metabolize apolipoprotein A1, which prepares a suitable microenvironment with low apolipoprotein A1 levels for successful implantation [13]. In an in vitro experiment, apolipoprotein A1 was also found to be have a higher expression in nondecidualized cells compared to decidualized stromal cells [14]. Thus, important negative effects can be predicted for apolipoprotein A1 in the initiation and maintenance of the window of implantation.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is present in 1-10% of unselected population, 2-8% of infertile women and 5-10 % of women with the history of miscarriage. [2][3][4][5][6][7][8][9][10][11][12] The wide range of difference in the prevalence rate is presumably because of use of different classification systems and non-uniform diagnostic tests. 13 Normal development of the female reproductive tract involves a series of complex processes which includes differentiation, migration, fusion and canalization of the Mullerian system.…”
Section: Introductionmentioning
confidence: 99%